EFL Students’ Critical Thinking and Their Reading Comprehension Ability: A Study Case Of Students In SMP Negeri 2 Baubau - Baharudin Adu; Nur Melansari; Fatima Azzahra (Surakarta English and Literature Journal, 2023)
ABSTRACT The purpose of this study was to determine whether there was a relationship between students' critical thinking skills and their capacity for reading comprehension. This study employed the ex-post facto research design as a quantitative approach, and the population of this study consisted of 345 eighth graders from SMP Negeri 2 Baubau, the sample consisted of 50 EFL students from the overall population, which was drawn using a straightforward random sampling procedure, tests and questionnaires served as the research's instruments. The findings of the investigation can be concluded that there was a strong relationship between the capacity of EFL students to think critically and their comprehension of reading. It is suggested that EFL students develop their critical thinking skills because they are necessary for reading comprehension as well as other language skills in language learning.